2001
DOI: 10.1023/a:1013123915272
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In establishing decision models in the treatment and prevention of breast cancer, it is important to evaluate patients' preferences for such interventions. The objectives of the present study were: (i) to characterize women's preferences for breast cancer treatments and BRCA1/BRCA2 testing, using the rating scale and standard gamble techniques; and (ii) to identify factors associated with these quality of life indices. Data were collected from women with breast cancer (n = 60), high-risk relatives of women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The result is in line with the findings of previous studies on genetic testing (albeit not specifically related to pharmacogenomics), indicating acceptance of genetic testing, particularly among patients who are ill or at-risk persons [13,14,15]. …”
Section: Discussionsupporting
confidence: 89%
“…The result is in line with the findings of previous studies on genetic testing (albeit not specifically related to pharmacogenomics), indicating acceptance of genetic testing, particularly among patients who are ill or at-risk persons [13,14,15]. …”
Section: Discussionsupporting
confidence: 89%
“…It is not surprising that both groups rated the screening modalities higher than the other conditions. A study by Cappelli et al of breast cancer patients, high-risk relatives, and a general population group also found that utilities varied inversely with invasiveness and that in all groups monitoring received the highest utility ranking [8].…”
Section: Discussionmentioning
confidence: 93%
“…Currently, the option or combination of options that is most effective in preventing cancer or cancer mortality is not known [7]. Moreover, each choice has physical, psychological and social consequences that vary among individuals and by circumstances such as age, income, or having young children [8][9][10]. Policy makers increasingly recognize the importance of considering such effects on health-related quality of life in their decisionmaking about these interventions [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the Schleinitz general population study using SG, the mean utility values in stages I–IV without estrogen receptor and IV with estrogen receptor were 0.68, 0.61, 0.56, 0.42, and 0.41, respectively 17. Cappelli et al27 compared women’s preferences for breast cancer treatment between breast cancer patients, high-risk relatives, and general population. The mean utility values of lumpectomy and radiation were 0.78, 0.73, and 0.68 in cancer patients, high-risk relatives, and general population, respectively, similar to utility of our scenario 3 (mean =0.779) 27.…”
Section: Discussionmentioning
confidence: 99%
“…Cappelli et al27 compared women’s preferences for breast cancer treatment between breast cancer patients, high-risk relatives, and general population. The mean utility values of lumpectomy and radiation were 0.78, 0.73, and 0.68 in cancer patients, high-risk relatives, and general population, respectively, similar to utility of our scenario 3 (mean =0.779) 27. In the study by Shih et al28 of oncology nurses, median utility values ranged from 0.299 to 0.371 in distant recurrence health states and from 0.336 to 0.376 in loco-regional recurrence health states.…”
Section: Discussionmentioning
confidence: 99%